Pedagogik/Ilmu Mendidik dalam Perspektif Guru Mata Pelajaran dan Guru Bimbingan dan Konseling - Andar Ifazatul Nurlatifah; Sai Handari (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2023)
This descriptive qualitative study aims to describe the meaning of pedagogic from the perspective of subject teachers and guidance and counseling teachers. Primary data related to the meaning of the teaching profession, pedagogical practices, and students were obtained through interviews with teachers at SMPN 1 Bansari and MTsN 1 Temanggung. Data triangulation was carried out by interviewing students and observing the academic culture at school. The results show that the teacher's view of pedagogy is in accordance with the concepts of tarbiyah, ta'dib, ta'lim, and tadrib according to Athhiyah al Abrasyi and the concept of changing culture to support the educational process according to Benitez.